Qualidade educacional: análises sobre a eficiência dos municípios cearenses - Rodrigues, Rafael de Oliveira (2019)
The discussions on inefficiency in the area of education in Brazil include factors such as faculty, investments, school infrastructure, socioeconomic profile of the student, number of schools in the region, among others. Such factors should have an influence on educational quality, which is usually expressed through standardized tests. Thus, this study intends to analyze the efficiency of the municipalities of Ceará on the performance of students in the tests of Spaece and Prova Brasil, using inputs such as the quality of the teacher, measured by the schooling of the same, the values given to the municipality for education expenses, the rate of sanitary sewage, the rate of water supply, among other variables. The data will be from the FUNDEB onlendings and other expenses for education were obtained together with the National Treasury Secretariat, while the school supply indicators are available in the School Census, and the other information by the Human Development Atlas of PNUD. The data were organized in a cross-sectional cohort for the year 2015, and the Data Envelopment Analysis model was estimated. Our results show that, in addition to a correlation between the results of the Prova Brasil and Spaece, we found a total of 43 municipalities operating efficiently in relation to the Spaece test scores, and 36 in relation to the Prova Brasil scores.